O conceito de participação da família no cenário político-educacional em São Paulo na década de 90 e o olhar de pais atores dos movimentos populares de São Mateus - Santos, Maria Lucia Salgado Cordeiro dos (2005)
The aim of this paper is to analyze the sense attributed to the concept of the family participation in the school during the nineties. In order to do this, it studies the public politics of that decade, from the federal ambit, to understand the dimensions of the municipal and the state spheres in São Paulo. Objectifying to compare the concept of the participation inside the public politics with the students parents concept involved in the family participation in the school, it shows the interviews with four students parents who performed different forms in the educational politics in São Mateus, a city district in São Paulo. Among these four, there is the testimony of the researcher herself, including the two moments. The first two interviews are from participants who acted in the deliberative School Council in 1991/93. The other two interviewed were selected by their participation in the neighborhood movement of parents that was organized to avoid the students transference during the stablishment of the state web reorganization in 1996. The result of this research is the sense of the participation in the educational public politics in the nineties and the sense for parents who desire both quantity and quality intended by the population in São Paulo for decades